Rational choice of social group size in mosquitofish. (2nd January 2019) - Reding, Luke; Cummings, Molly E.
Abstract : Choice of social group can affect the likelihood of survivorship and reproduction for social species. By joining larger social groups—shoals—small freshwater fish like the mosquitofish Gambusia affinis can reduce predation risk and forage more efficiently. We tested shoal choice in mosquitofish to determine whether such choices are economically rational, i.e. consistent and optimal. Although many studies of decision-making assume rational choice, irrational decision-making is common and occurs across contexts. We tested rationality of shoaling decisions by testing the constant ratio rule, which states that the relative preference for two options should not change in the presence of a third option. Female mosquitofish upheld this rule when tested for shoal preference based on group size. Our results contrast with other studies showing violations of the constant ratio rule in foraging and mate choice decision-making contexts. These results suggest that decisions that immediately influence survivorship or decision-making along a single dimension may favour rational decision-making.